Physiology of midbrain head movement neurons in cervical dystonia. Issue 6 (20th February 2017) - Sedov, Alexey; Popov, Valentin; Shabalov, Vladimir; Raeva, Svetlana; Jinnah, H. A.; Shaikh, Aasef G.
ABSTRACT: Background: Early theories for cervical dystonia, as promoted by Hassler, emphasized the role of the midbrain interstitial nucleus of Cajal. Focus then shifted to the basal ganglia, and it was further supported with the success of deep brain stimulation. Contemporary theories suggested the role of the cerebellum, but even more recent hypotheses renewed interest in the midbrain. Although the pretectum was visited on several occasions, we still do not know about the physiology of midbrain neurons in cervical dystonia. Methods: We analyzed the unique database of pretectal neurons collected in the 1970s and 1980s during historic stereotactic surgeries aimed to treat cervical dystonia. This database is valuable because such recordings could otherwise never be obtained from humans. Results: We found the following 3 types of eye or neck movement sensitivity: eye‐only neurons responded to pure vertical eye movements, neck‐only neurons were sensitive to pure neck movements, and the combined eye‐neck neurons responded to eye and neck movements. There were the 2 neuronal subtypes: burst‐tonic and tonic. The eye‐neck or eye‐only neurons sustained their activity during eccentric gaze holding. In contrast, the response of neck‐only and eye‐neck neurons exponentially decayed during neck movements. Conclusions: Modern quantitative analysis of a historic database of midbrain single units from patients with cervical dystonia might support novel hypotheses for normal and abnormal head movements. This data, collected almost 4 decades ago, must be carefully viewed, especially because it was acquired using a less sophisticated technology available at that time and the aim was not to address specific hypothesis, but to make an accurate lesion providing optimal relief from dystonia. © 2017 International Parkinson and Movement Disorder Society